Oxynoemacheilus cilicicus, a new nemacheilid loach from the Göksu River in southern Anatolia (Teleostei: Nemacheilidae) - Kaya, Cüneyt; Turan, Davut; Bayçelebi̇ Esra; Kalayci, Gökhan; Freyhof, Jörg (Zootaxa, 2020)
Oxynoemacheilus cilicicus, new species, is described from the Göksu, Seyhan and Ceyhan rivers in southern Turkey. It is distinguished from other Oxynoemacheilus species in the Eastern Mediterranean Sea basin by possession of an incomplete lateral line, terminating before the vertical of the dorsal-fin origin or slightly behind the dorsal-fin base, a deeply emarginate caudal fin, no suborbital groove in male individuals, and a series of dark-brown bars on the flank not interrupted along the lateral line. Molecular data suggest that Oxynoemacheilus cilicicus is characterised by 22 variable nucleotide substitutions and a minimum K2P distance of 4.09% with O. panthera in the mtDNA COI barcode region.